Parametric Study on Steel Girders with Corrugated Webs - Muhammad Shukry; Tarek Sharaf; Ashraf Elsabbagh; Mohamed Elghandour (Port Said Engineering Research Journal, 2020)
I-shaped Steel Girder with Corrugated Webs [SGCW] are used in steel structures because of their notable advantages. SGCW permit using a thin web plate without using stiffeners. This girder is useful for eliminating the use of stiffeners and larger thickness that contribute to the reduction in the weight and the cost of the girder. In this paper, a numerical study based on the Finite Element Analysis [FEA] was conducted to predict the behavior of SGCW. The verification study was conducted for previous experimental tests. Based on the previous investigations, the parametric study was carried on to investigate the actual behavior of SGCW with different parameters such as the web thickness, the girder height, the web shapes, and the corrugated angles under different loads. The results of the parametric study showed the effect of each parameter on the overall load carrying capacity of the beams and indicated that the corrugated angle is the most effective parameters for SGCW